Method for identification of condition-associated public antigen receptor sequences - Pogorelyy, Mikhail V; Minervina, Anastasia A; Chudakov, Dmitriy M; Mamedov, Ilgar Z; Lebedev, Yuri B; Mora, Thierry; Walczak, Aleksandra M (eLife, 2018)
Diverse repertoires of hypervariable immunoglobulin receptors (TCR and BCR) recognize antigens in the adaptive immune system. The development of immunoglobulin receptor repertoire sequencing methods makes it possible to perform repertoire-wide disease association studies of antigen receptor sequences. We developed a statistical framework for associating receptors to disease from only a small cohort of patients, with no need for a control cohort. Our method successfully identifies previously validated Cytomegalovirus and type one diabetes responsive TCR[Formula: see text] sequences .
Keywords: receptory antigenů T-buněk; vysoce účinné nukleotidové sekvenování; Complementarity Determining Regions; Cytomegalovirus; receptory antigenů B-buněk; Adaptive Immunity; computational biology; systems biology; Diabetes Mellitus; Receptors, Antigen, T-Cell; hypervariabilní oblasti; Humans; statistical analysis; human; immunology; genetická variace; receptory imunologické; Receptors, Antigen; Receptors, Immunologic; diabetes mellitus; repertoire sequencing; condition associated receptors; lidé; inflammation; High-Throughput Nucleotide Sequencing; Receptors, Antigen, B-Cell; Genetic Variation; adaptivní imunita; receptory antigenů